2016
DOI: 10.1371/journal.pone.0145771
|View full text |Cite
|
Sign up to set email alerts
|

Development and Measurement of Guidelines-Based Quality Indicators of Caesarean Section Care in the Netherlands: A RAND-Modified Delphi Procedure and Retrospective Medical Chart Review

Abstract: BackgroundThere is an ongoing discussion on the rising CS rate worldwide. Suboptimal guideline adherence may be an important contributor to this rise. Before improvement of care can be established, optimal CS care in different settings has to be defined. This study aimed to develop and measure quality indicators to determine guideline adherence and identify target groups for improvement of care with direct effect on caesarean section (CS) rates.MethodEighteen obstetricians and midwives participated in an exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In the CS implementation study (SIMPLE), a RAND-modified Delphi procedure resulted in 27 quality indicators describing optimal CS care based on international guidelines and literature [13]. The adherence to CS quality indicators was measured in 21 hospitals in The Netherlands in order to gain insight into current obstetrical care.…”
Section: Introductionmentioning
confidence: 99%
“…In the CS implementation study (SIMPLE), a RAND-modified Delphi procedure resulted in 27 quality indicators describing optimal CS care based on international guidelines and literature [13]. The adherence to CS quality indicators was measured in 21 hospitals in The Netherlands in order to gain insight into current obstetrical care.…”
Section: Introductionmentioning
confidence: 99%
“…The study was a consecutive study of the previously reported SIMPLE study [8]. The study was initially designed as a controlled before and after study with an intervention trial incorporated in the second part.…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, 1.3 million women in the US underwent a CS (32%) [6], making it one of the most frequently performed operative interventions in women. In The Netherlands, VBAC rates are much higher (54%) [7], but most women are inadequately informed about their choices due to caregivers’ fear of an increase in CS rates [8]. Morbidity risks (both maternal and neonatal) are directly related to the individual probability of VBAC since morbidity is lowest in women with VBAC, but higher in women with unplanned than planned CS [9].…”
Section: Introductionmentioning
confidence: 99%
“…If we implement a standardized system where labor outcomes are included, we may more easily recognize events and adverse outcomes in the delivery ward 264,317,318 . An improvement of the use of TGCS as a standardized system including labor outcomes was introduced in Paper II.…”
Section: Systems and Standardizationmentioning
confidence: 99%
“…Oxytocin augmentation has thereby gained focus, and awareness has been raised. It is believed that such projects will contribute to increased quality of labor management 317 . In the meantime, obstetricians and midwives should collaborate and improve the available assessment tools 293,320 .…”
Section: Systems and Standardizationmentioning
confidence: 99%